New tests of cumulative prospect theory and the priority heuristic: Probability-outcome tradeoff with branch splitting - Michael H. Birnbaum (Judgment and Decision Making, 2008)
Previous tests of cumulative prospect theory (CPT) and of the priority heuristic (PH) found evidence contradicting these two models of risky decision making. However, those tests were criticized because they had characteristics that might “trigger” use of other heuristics. This paper presents new tests that avoid those characteristics. Expected values of the gambles are nearly equal in each choice. In addition, if a person followed expected value (EV), expected utility (EU), CPT, or PH in these tests, she would shift her preferences in the same direction as shifts in EV or EU. In contrast, the transfer of attention exchange model (TAX) and a similarity model predict that people will reverse preferences in the opposite direction. Results contradict the PH, even when PH is modified to include a preliminary similarity evaluation using the PH parameters. New tests of probability-consequence interaction were also conducted. Strong interactions were observed, contrary to PH. These results add to the growing bodies of evidence showing that neither CPT nor PH is an accurate description of risky decision making.